Molecular cloning, mRNA expression and biological activity of the pheromone biosynthesis activating neuropeptide (PBAN) from the European corn borer, Ostrinia nubilalis. Issue 5 (21st June 2017) - Fodor, J.; Köblös, G.; Kákai, Á.; Kárpáti, Z.; Molnár, B. P.; Dankó, T.; Bozsik, G.; Bognár, C.; Szőcs, G.; Fónagy, A.
Abstract: Pheromone biosynthesis activating neuropeptide (PBAN) is a member of the pyrokinin (FXPRLamide) insect neuropeptides. Here, we report the cloning of the gene Ostnu‐PBAN from the E and Z pheromone strains of the European corn borer (ECB), Ostrinia nubilalis (Lepidoptera: Crambidae), a major pest of maize. The Ostnu ‐ PBAN genomic sequence is > 5 kb in length and consists of six exons. The deduced amino acid sequence revealed a 200‐residue precursor protein including a signal peptide, a 24‐amino acid (aa) diapause hormone, a 37‐aa PBAN and three other FXPRLamide neuropeptides. Our in vivo assays suggest that the 37‐aa synthetic Ostnu‐PBAN is hormonally active in the pheromone gland. It restores sex pheromone production to normal levels in mated females and decapitated virgins of both E and Z cultures. The results of a real‐time PCR analysis indicated that Ostnu‐PBAN mRNA levels reached a plateau in the brain‐suboesophageal ganglion complexes 1 day after eclosion, and mating did not affect the mRNA expression. Three size classes of Ostnu ‐ PBAN mRNA (1.9, 2.0 and 2.1 kb) were obtained, differing only in the length of the 3′ untranslated region. However, there was no correlation between sequence divergence and the pheromone composition, voltinism or geographical origin (Hungary, Slovenia, Sweden, Turkey) of ECB moths.